Teaching Reading Comprehension and Small Group Discussion at the Second Grade Student of MTS Al – Ikhlas In Academic Year 2021/2022 - Wahab, Abdul; Putraidi, Karyawan (HAMJAH DIHA FOUNDATION bekerjasama dengan PENA INSTITUTE, 2022)
The aim of this research is how to find out a relevant method to teach the students on reading comprehension for the second year students of MTS Al-Ikhlas, Pandan Tinggang, Batu Jangkih, Southwest Praya of central Lombok in academic year 2021/2022.This research is used reading comprehension and small group discussion in teaching reading comprehension. The kind of this research is a classroom action research (CAR). The populations of this research were all students of the second grade student of MTS Al-Ikhlas that consists of 16 students. Meanwhile the subject research was VIIa because they were less in comprehension of the text through reading activity, then the technique of collecting data was observation and test. In addition in analyzing the numerical data, the writer gained the average students score in each cycle. The use of small group discussion in teaching is able to improve the students’ English reading skills. It is proved that students score at the second cycle is higher than at the first cycle; the mean score of the first cycle were 5.73 and at the second cycle were 7.48, and the curriculum standar of Minimum Completness Criteria (MCC) at the first cycle were 53.57% it had not reached yet the classical sucsessful criteria,because the classical successful learning must be >60% and at the second cycle were 71.42%,so it can be said succes because 71.42% of the students got >60. The use of small group discussion in teaching students’ reading comprehension can motivate the students to be more active and contribute positive effect to their development of learning process.